أهم المشاكل الاجتماعية والنفسية المؤدية إلى الإصابة بمرض الزهايمر لدى كبار السن (دراسة ميدانية لعينة من المصابين في مدينة بغداد) (Journal Of Educational and Psychological Researches, 2017)
The most important social and psychological problems that lead to Alzheimer's disease in the elderly (field study of a sample of people living in the city of Baghdad). The research aims to: 1. Identify the most important social, psychological and health problems of elderly people with Alzheimer's disease. 2. The most prominent solutions and treatments for people living with this disease. 3. rehabilitation and provision of social, psychological and medical services for people with Alzheimer's disease. The research stages of Alzheimer's disease and its symptoms and the most important causes of Alzheimer's disease, research has strengthened the theoretical framework. The theoretical study unexplained social pressure generating dealt with Alzheimer's disease, and also offered to study the social factors that contribute to the reduction of the incidence of Alzheimer's disease, and how social adjustment with Alzheimer's disease. Eating systematic side to look more than a tool for data collection in order to have a sound scientific information, and tools that pillars study in this research are: 1. resolution 2. Interview The most important findings of the research: 1. The percentage of care for children and their parents a patient with Alzheimer's disease (44%) of the surveyed sample. 2. The proportion of respondents who have been subjected to psychological trauma as a result of the loss of a family member (42%). 3. The proportion of respondents who have been exposed to trauma resulting from war (22%). 4. The proportion of respondents who are solving their social problems with the help of the family (48%), friends (22%), and address the respondent to the problems suffered by himself (44%). 5. Treatment methods that reduce the severity of the disease, drug therapy (23%), and social intervention (30%), and those who do not believe in therapy and were treated in ways that the disease is hereditary (24%). 6. Patients who have difficulty adapting to new social situations proportion (58%). 7. patients who suffer from difficult to accomplish everyday tasks without the help of others rate (1.8%). 8. Patients who suffer from the problem of social isolation ratio (76%). The most important conclusions: 1. Contributed to the exceptional circumstances that ravaged Iraq to contribute significantly to family disintegration and lack of communication between parents and children. 2. The inability of the patient are necessary in dealing with advanced cases which require intervention in care of by official institutions contribute to ease the burden and rehabilitation care. The study also found that many of the recommendations that will help the elderly to facilitate the provision of health and therapeutic services that contribute to the rehabilitation him healthy and myself properly